2017
DOI: 10.4172/2254-609x.100046
|View full text |Cite
|
Sign up to set email alerts
|

A Comperative Evaluation of 3 Different Polishing Methods on Tooth Surface Roughness

Abstract: Objective: The objective of this study is to evaluate the effect of three different polishing procedures on surface roughness occuring after sonic scaling. Material and Methods:Dental calculus on 60 extracted teeth stored in distilled water was removed using a sonic device. Surface roughness was measured by profilometer and then samples were divided into 3 groups. Polishing was applied to the samples in first group by rotary rubber cup and prophylaxis paste, to the samples in second group by air-flow, and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies 2,18,[20][21][22] showed that pogo bur produced a smoother enamel surface than tungsten carbide bur. Studies 17,20,[23][24][25] comparing tungsten carbide bur and stainbuster bur shows that stainbuster bur produces the smoothest enamel surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies 2,18,[20][21][22] showed that pogo bur produced a smoother enamel surface than tungsten carbide bur. Studies 17,20,[23][24][25] comparing tungsten carbide bur and stainbuster bur shows that stainbuster bur produces the smoothest enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 2,18,[20][21][22] showed that pogo bur produced a smoother enamel surface than tungsten carbide bur. Studies 17,20,[23][24][25] comparing tungsten carbide bur and stainbuster bur shows that stainbuster bur produces the smoothest enamel surface. Priyanka shah et al conducted studies comparing stainbuster bur and pogo bur and they concluded that stainbuster bur produces the smoothest enamel surface when compared to pogo bur.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the polishing process is a necessary step in order to reduce the surface roughness resulting from the scaling and root planning process [24][25][26]. In this regard, it was decided to test erythritol, glycine and sodium bicarbonate powders on enamel.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was decided to test erythritol, glycine and sodium bicarbonate powders on enamel. Moreover, it has been shown that air polishing is the most effective polishing method in terms of reducing time and costs [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation